Kontruksi Budaya PATRIARKHI Bagi Perempuan di Indonesia dan India - Ummu Kulsum (Proceedings of Annual Conference for Muslim Scholars, 2017)
This unique woman has always been the subject of discussion in all walks of life, with the theory of nurture and nature. The meaning of the "Patrtiarkhi" language of Meriam Johnson puts the origin of gender imbalances in the patriarchal family structure (patriarchal) presented in the public order. While families have different functions in economic institutions and other public institutions. Cultural and institutional coercion requires women to be weak and always succumb to relationships with their husbands, on the other hand experiencing competition in earning a living in the domestic order. Patriarchal understanding, has a tremendous impact in the world community, not least in Indonesia and India. No one is suing with the meaning of patriarchy. It's just how to position women, in order to be accepted from the text of texts Religion, culture, and social, political and economic structure.Keywords: Patriarchy, Islamic Education and Women.